2018
DOI: 10.1177/0361198118796928
|View full text |Cite
|
Sign up to set email alerts
|

Unrevealed Preferences: Unexpected Traveler Response to Pricing on Managed Lanes

Abstract: This paper addresses priced managed lane corridors, on which travelers may choose to pay a toll to travel on the managed lanes (MLs) to realize generally faster, more reliable travel than on the adjacent, toll-free general purpose lanes (GPLs). These lanes exist in many cities across the United States and are becoming more common as transportation agencies look for innovative ways to increase capacity and regulate demand for their roadways. Commonly, demand for these lanes is modeled assuming travelers choose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 8 publications
2
28
0
Order By: Relevance
“…Note that this change assumes all travelers make economically rational decisions based on their VTT. It has been shown that most travelers do not (27,47) and that many travelers feel they save more travel time on MLs than is the case (45). Therefore, the assumption of economically rational decision making is likely inaccurate and revenue loss is probably not as high as 17.4%.…”
Section: Resultsmentioning
confidence: 99%
“…Note that this change assumes all travelers make economically rational decisions based on their VTT. It has been shown that most travelers do not (27,47) and that many travelers feel they save more travel time on MLs than is the case (45). Therefore, the assumption of economically rational decision making is likely inaccurate and revenue loss is probably not as high as 17.4%.…”
Section: Resultsmentioning
confidence: 99%
“…However, in the context of managed lanes, several studies have found that how travelers actually make choices deviates from the presumptions and conclusions of many SP studies. In contrast to SP studies, it has been observed that in real choice situations travel time information is not always available and used (24), and some travelers might persistently make the same choice (14).…”
Section: Xie Et Almentioning
confidence: 96%
“…Introduction of the loyalty variable was inspired by the data-driven analysis carried out by Burris and Brady (14). Based on data collected from Katy Freeway and the North Tarrant Express, they found that most travelers on these freeways always used the same type of lanes regardless of travel time and toll.…”
Section: Variable Personalizationmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the revenue generated from tolling is necessary for funding the system through the dynamic toll pricing. Dynamic tolls alter according to the traffic conditions along the facility and the time saved using MLs ( 8 ). For example, the toll price increases in congestion conditions to maintain the traffic flow in the facility ( 9 ).…”
Section: Managed Lanesmentioning
confidence: 99%